2006
DOI: 10.1016/j.febslet.2006.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Localization and in vitro binding studies suggest that the cytoplasmic/nuclear tobacco lectin can interact in situ with high‐mannose and complex N‐glycans

Abstract: The possible in vivo interaction of the Nicotiana tabacum agglutinin (Nictaba) with endogenous glycoproteins was corroborated using a combination of confocal/electron microscopy of an EGFP-Nictaba fusion protein expressed in tobacco Bright Yellow-2 (BY-2) cells and biochemical analyses. In vitro binding studies demonstrated that the expressed EGFP-Nictaba possesses carbohydrate-binding activity. Microscopic analyses confirmed the previously reported cytoplasmic/nuclear location of Nictaba in jasmonate-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 22 publications
1
45
0
1
Order By: Relevance
“…These results are in agreement with previous observations that showed the specific interaction of Nictaba with GlcNAc oligomers (Lannoo et al, 2006b). Future studies will concentrate on the ultrastructural colocalization of Nictaba and histone proteins in the plant cell and the functional implications resulting from this interaction.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results are in agreement with previous observations that showed the specific interaction of Nictaba with GlcNAc oligomers (Lannoo et al, 2006b). Future studies will concentrate on the ultrastructural colocalization of Nictaba and histone proteins in the plant cell and the functional implications resulting from this interaction.…”
Section: Resultssupporting
confidence: 92%
“…The extracellular compartment of plant cells contains many heavily glycosylated proteins (Knox, 1995;Jose-Estanyol and Puigdomenech, 2000;Léonard et al, 2002). Taking into account the carbohydratebinding properties of Nictaba as determined by glycan array analyses (Lannoo et al, 2006b), it is not surprising that these proteins are retained on the lectin column. Therefore, a more rigid purification and fractionation of tobacco cells was performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If high-Man glycoproteins are also present in Hessian fly larval salivary glands or gustatory receptors, then it is conceivable that high concentrations of His 6 -HFR1 may act as an antifeedant by binding to these structures; thus, they would not be ingested. His 6 -HFR1 does not require the core di-GlcNAc of the N-glycans for binding (Supplemental Table S1), as required by some other high-Man N-glycan-binding lectins such as tomato (Solanum lycopersicum) lectin (Lycopersicon esculentum agglutinin; Oguri, 2005) and tobacco (Nicotiana tabacum) lectin (Nicotiana tabacum agglutinin; Chen et al, 2002;Lannoo et al, 2006). The positive hemagglutination activity suggested that the presence of the His tag did not interfere with His 6 -HFR1 function (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%